Pemanfaatan Analytical Hirarchy Process untuk Penentuan Karakteristik Combat Aircraft dalam Rangka Mendukung Industri Pertahanan Nasional - Ahmad Afandi; Dwi Soedianto; Edy Iwan Bangun (Universitas Trunojoyo Madura, 2022)
The Indonesian Air Force is the main combat tool in the use of force to defend the sovereignty and territorial integrity of the Unitary State of the Republic of Indonesia as a unit in order to achieve guarantees for the safety of the nation and state. Indonesia only relies on 33 F-16 AM, BM, C and D aircraft, which are more than 30 years old. Then 16 Sukhoi 27 and 30 aircraft with almost 20 years of age as the main fighter aircraft. The limited number of aircraft spare parts as well as the limited types and number of guided missiles also caused the combat readiness of the F16 and Sukhoi 27 and 30 aircraft to be not optimal. The F5 Tiger fighter has fallen out of service in recent years and there has been no replacement to date. Likewise, the Hawk 100/200 aircraft which are more than 25 years old. the obligation of the Ministry of Defense to plan the purchase of fighter aircraft that will operate until 2030 and 2040. This research will use the Analytical Hierarchy Process (AHP) method to determine the choice of Combat Aircraft with predetermined criteria with the alternative choice of Dassault Rafale fighter aircraft from France, the Su 35 Russian-made and US-made F-15 EX aircraft. The highest data processing results are Dassault Rafale 63.7%, Su 35 20.3% and F-15 EX 16%. The result of the Multirole Combat Aircraft selection is that the Dassaut Rafale is selected. with an Inconsistency value of 0.04. This shows that the alternative calculation is still within the inconsistency threshold, which is less than 0.1. With the election of Dassault Rafale, it is hoped that the Transfer of Technology with PT. Indonesian Aerospace in order to increase the capability of the Domestic Defense Industry, especially the Air Force. later PT DI will be directly involved in the Maintenance, Repair, and Overhaul (MRO) process, including the preparation of the supporting infrastructure